2018
DOI: 10.1099/jgv.0.000965
|View full text |Cite
|
Sign up to set email alerts
|

Recent US bluetongue virus serotype 3 isolates found outside of Florida indicate evidence of reassortment with co-circulating endemic serotypes

Abstract: Since 1999, 11 serotypes of bluetongue virus (BTV) similar to Central American or Caribbean strains have been isolated in the southeastern United States, predominantly in Florida. The majority of the incursive serotypes have remained restricted to the southeastern US. In recent years, BTV serotype 3 (BTV-3) has been isolated in areas increasingly distant from Florida. The current study uses whole genome sequencing of recent and historical BTV-3 isolates from the US, Central America and the Caribbean with addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
(25 reference statements)
0
24
0
Order By: Relevance
“…The BTV genome consists of 10 linear segments of double-stranded RNA, and in tissue culture, these segments have been demonstrated to be exchanged with few constraints between European strains of BTV serotype 1 (BTV-1) and BTV serotype 8 (BTV-8) [14]. Analysis of full genome sequences from across European strains of BTV has highlighted that this phenomenon occurs frequently but may also be subject to specific selective pressures that are not fully understood [13,52,53]. Reassortment of BTV strains in the ruminant host were studied in vivo in the USA during the 1980s in both ruminants and vectors [40,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…The BTV genome consists of 10 linear segments of double-stranded RNA, and in tissue culture, these segments have been demonstrated to be exchanged with few constraints between European strains of BTV serotype 1 (BTV-1) and BTV serotype 8 (BTV-8) [14]. Analysis of full genome sequences from across European strains of BTV has highlighted that this phenomenon occurs frequently but may also be subject to specific selective pressures that are not fully understood [13,52,53]. Reassortment of BTV strains in the ruminant host were studied in vivo in the USA during the 1980s in both ruminants and vectors [40,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…The strain of BTV-2 isolated in California is a reassortant of BTV-2 and BTV-6, the latter a previously exotic serotype to North America (50). Similarly, strains of BTV-3 that have recently expanded their range beyond the southeastern US are able to readily reassort with BTV strains historically enzootic in the US (51). Recent studies based on BTV field isolates have shown reassortment is common and may drive phenotypic change resulting in a fitness advantage for the virus (46,48,49,52).…”
Section: Bluetongue Virusmentioning
confidence: 99%
“…In spite of a long history of BTV-3 infections in ruminants in South Africa, India, Caribbean and Northern America (41,42,56,57), epidemiological data as well as information on pathogenicity and infectivity of BTV-3 infection from these regions are absent or scarce. Even if it was not possible to evaluate their pathogenicity in cattle and goats, this paper still gives important information on the possible origin of the BTV-AUTHOR CONTRIBUTIONS GK, JV, IS, SS, AM, ID, IG, AK, OK, and EO collected field samples and epidemiological data.…”
Section: Discussionmentioning
confidence: 99%
“…1st cluster includes strains originated from Africa, Mediterranean Basin and North America (western topotypes, w); 2nd-includes strains originated from Japan, India, and Australia (eastern topotypes, e). The nucleotide (nt) identity between Western and Eastern topotype Seg-2 can be as small as 71.5% (7,(38)(39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%